Design and Evaluation of Sustained Release Chitosan Coated Phenylephrine Hydrochloride Microcapsules - SANEHI PARVISH KUMAR; MUKHERJEE SWARUPANANDA; VISHWANATH B.A (International Journal of Pharma and Bio Sciences, 2010)
The present research work was undertaken to formulate and evaluate sustained release coated microcapsules of Phenylephrine HCl for 24 hours. Phenylephrine HCl is sympathomimetic vasoconstrictor that has been used as a nasal decongestant, having a half life of 2.5±0.5 hours and enhance frequent dosing is required to maintain therapeutics plasma concentration. Therefore, sustained release microcapsulated dosage form of Phenylephrine HCl having a release profile upto 24 hours, decrease the frequent dosing and will maintain steady state therapeutics plasma concentration which will also greatly improve patient compliance. Phenylephrine HCl was complexed with cationic resin that is Amberlite IR-120 and then coated with ethylcellulose to obtain microencapsulated resinate which will be having a release profile up to 24 hours. Chitosan coating was further given to microcapsulated resinate to increase the transit time of the dosage form in the GIT. The optimized formulation was achieved with the ratio 1:2.5 of drug-resin complex and coat/core ratio of 1:2 having 6% w/v ethylcellulose. The bioadhesive coating of chitosan was found to be optimum with 1% w/v concentration.